Changes in Perceptions of Couples of Childbearing Age in Indonesian Family Planning Mentoring Program - Lagu, Abdul Majid H.R.; Habibi, Habibi (Diversity: Disease Preventive of Research Integrity, 2021)
The family planning program in general forms a small family according to the socio-economic strength of a family by controlling the birth of a child, to obtain a happy and prosperous family that can meet their daily needs. on the Family Planning Program in Gowa Regency. The type of research used in this study is a quasi-experiment to determine the effectiveness of assistance in increasing the participation of fertile age couples (PUS) in the family planning program located in Batangkaluku Village, Somba Opu District, Gowa Regency. The population in this study were all fertile age couples (PUS) in the area of Batangkaluku Village, Somba Opu District, Gowa Regency, totaling 1,537 people. The number of samples in this study was 94 Fertile Age Couples (PUS). The research instrument used in this study is a questionnaire containing several questions to obtain accurate and objective data on the problems being studied. The results showed that there are factors that influence the participation of fertile age couples (PUS) in the family planning program, namely knowledge, self-efficacy, access to family planning services, support for family planning officers, and husband's support. This study recommends health workers increase the frequency of conducting family planning counseling to increase knowledge of contraceptives in the community.